MAKNA INVESTASI PADA ANAK DALAM MITOS “BANYAK ANAK BANYAK REZEKI” : STUDI FENOMENOLOGI - Vinny Syifa Denada; Ali Fikri; Ayudia Sokarina (Jurnal Ilmiah Akuntansi Peradaban, 2022)
The purpose of this study was to reveal the meaning of investment on children in “banyak anak banyak rezeki” myth through education. This study was employed interpretative paradigm with phenomenology as methodology. The author interviewed three informants in West Lombok District which are householder who worked as a pedagogue. The result has found two categories the significance of investment on children, material and non-material significance. Materially, the investment on children provided a very high amount of return to the parents so that it gave them a secure feeling financially in their old age. Whereas non-materially, the investment on children provided a return in the form of happiness in this world and the hereafter. Keywords : Investment, Phenomenology, Education, Return, Child